Academic Exchange and Outreach Projects: Reflexions from an Experience on Refugees, Homeless and Occupations in Brazil and France. - FIRMO, HELOISA TEIXEIRA (Revista Práxis, 2021)
Environmental engineering students conduct academic exchanges as part of their education. Refugees and homeless in many countries have in common the search for decent housing and basic survival conditions. Today’s serious socio-environmental problems must be addressed by professionals who are able to propose effective and lasting solutions. Thus, and seeking to contribute to a full citizen formation of the individual and engineer of today’s society, this article describes the experience of a French exchange student from EIVP (Ecole des Ingénieurs de Ville de Paris) in Environmental Engineering at UFRJ (Federal University of Rio de Janeiro) in the MUDA Outreach project, where the student had the opportunity to visit occupations supported by social movements in previously unoccupied places in the metropolitan region of Rio de Janeiro. From reflections on the concept of refugee in Brazil and France, were analyzed and compared initiatives of settlements and homeless in both countries. It is concluded that, although distinct, the displacement crises of individuals and families in both countries have several points in common, highlighting that successful solutions can occur when the main objective is to propose comprehensive social inclusion projects that begin with the consolidation of a new generation of global citizens, which is the main contribution of this work.